Expression profile and ligand‐binding characterization of odorant‐binding protein 2 from Batocera horsfieldi (Hope). (28th October 2014) - Li, H.; Pan, X.‐Y.; Chen, L.‐Z.; Zhang, A.; Wang, D.‐X.; Wang, M.‐Q.
Abstract Odorant‐binding proteins (OBPs) are important components in insect olfactory systems that transport semiochemicals through the aqueous sensillum lymph to surface of olfactory receptor neurons. In this study, we cloned the cDNA of odorant‐binding protein 2 (BhorOBP2) in Batocera horsfieldi (Hope) and measured the level of the BhorOBP2 mRNA in a variety of tissues using quantitative reverse transcription and real‐time polymerase chain reaction. We found that the BhorOBP2 mRNA was primarily expressed in the antennae, the level of BhorOBP2 mRNA was higher in males than in females, and correlated with age and mating status. The BhorOBP2 mRNA was also expressed in the labial palps at relatively high level, suggesting that it might have a role in gestation as well. To better understand the functions of the BhorOBP2 protein in odorant reception, recombinant BhorOBP2 was expressed in Escherichia coli, and the binding specificity of the protein for 18 volatile developmentally relevant chemicals and host‐plant‐related metabolites were assessed using N‐phenyl‐1‐naphthylamine as a fluorescent probe. Competitive fluorescence binding assays showed that BhorOBP2 bound a broad range of host‐plant‐related odorants, including (E)‐2‐hexenal, 2‐methyl‐butanal, salicylaldehyde, (1S)‐(‐)‐verbenone, (Z)‐3‐hexen‐1‐ol, (E)‐2‐hexen‐1‐ol, β‐pinene and ethyl acetate. Our results imply that BhorOBP2 might play an important role in the selectivity and specificity of odorant reception.